The Effect Of Entrepreneurial Self Efficacy And Entrepreneurial Creativity To Entrepreneurial Intention From Students In Tarumanagara University - Nandinto Martin; Hannes Oey Widjaja (Jurnal Manajerial Dan Kewirausahaan, 2019)
This study aimed to examine how an Entrepreneurial Self-efficacy, and Entrepreneurial Creativityaffect Entrepreneurial Intention. The sample in this study were 100 students in Tarumanagara University.. The sampling technique used is purposive sampling. Data collection technique used is questionnaire. The findings show that Entrepreneurial Self-efficacy and Entrepreneurial Creativitydid  affect Student’s Entrepreneurial Intention in Tarumanagara Univesity .